Unveiling Pharmacological Responses and Potential Targets Insights of Identified Bioactive Constituents of Cuscuta reflexa Roxb. Leaves through In Vivo and In Silico Approaches - Md. Adnan; Md. Nazim Uddin Chy; A.T.M. Mostafa Kamal; Md. Riad Chowdhury; Md. Shariful Islam; Md. Amzad Hossain; Abu Montakim Tareq; Md. Imam Hossain Bhuiyan; Md Nasim Uddin; Afroza Tahamina; Md Obyedul Kalam Azad; Young Seok Lim; et al. (MDPI AG, 2020)
Cuscuta reflexa Roxb. is traditionally used by the indigenous communities of Bangladesh to treat different diseases, such as pain, edema, tumor, jaundice, and skin infections. This study tested neuro-pharmacological, anti-nociceptive, and antidiarrheal activities by in vivo and in silico experiments for the metabolites extracted (methanol) from the leaves of Cuscuta reflexa (MECR). During the anxiolytic evaluation analyzed by elevated plus maze and hole board tests, MECR (200 and 400 mg/kg) exhibited a significant dose-dependent reduction of anxiety-like behavior in mice. Similarly, mice treated with MECR demonstrated a dose-dependent decrease in the time of immobility in both forced swimming and tail suspension tests. In addition, anti-nociceptive activity was assessed by the chemical-induced (acetic acid and formalin) pain models. In both cases, 400 mg/kg was found to be most effective and significantly (p < 0.001) inhibited acetic acid stimulated writhing and formalin-induced licking (pain response) in mice. Furthermore, antidiarrheal efficacy determined by the castor-oil induced diarrheal model manifested an evident inhibition of diarrheal stool frequency. In parallel, previously isolated bioactive compounds were documented based on the biological activities and subjected to in silico studies to correlate with the current pharmacological outcomes. The selected isolated compounds (15) displayed favorable binding affinities to potassium channels, human serotonin receptor, COX-1, COX-2, M3 muscarinic acetylcholine receptor, and 5-HT3 receptor proteins. Additionally, the ADME/T and toxicological properties were justified to unveil their drug-like properties and toxicity level. Overall, Cuscuta reflexa is bioactive and could be a potential source for the development of alternative medicine.